2009
DOI: 10.1111/j.1365-3156.2009.02422.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of house infestation dynamics by non-domiciliatedTriatoma dimidiatareveal a spatial gradient of infestation in rural villages and potential insect manipulation byTrypanosoma cruzi

Abstract: Summaryobjective Chagas disease is a major vector-borne parasitic disease in Latin America, primarily transmitted to humans by triatomine vectors. Non-domiciliated triatomine species such as Triatoma dimidiata in the Yucatan peninsula, Mexico, can transiently invade houses and are emerging as a major challenge to control Trypanosoma cruzi transmission to humans. We analyzed the spatio-temporal spreading of house infestation by T. dimidiata in four rural villages.methods Triatomines were collected in four rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 45 publications
4
70
1
Order By: Relevance
“…Natural infection rate is one important factor; several studies have reported a wide range of natural infection in T. dimidiata that varies from very low, such as 4%, to high natural infection, such as up to 34%. 3,4,16 For example, low natural infection of 4% has been found in sylvan populations of T. dimidiata in the Yucatan state, Mexico, whereas in the Peten, Guatemala, it can reach up to 25% in sylvan populations. 4,17 In this work, we found natural infection of 38%; these data are similar to those results in the work by Ramirez-Sierra and others, 3 which reported 34% natural infection in a rural community in the Yucatan state, Mexico.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural infection rate is one important factor; several studies have reported a wide range of natural infection in T. dimidiata that varies from very low, such as 4%, to high natural infection, such as up to 34%. 3,4,16 For example, low natural infection of 4% has been found in sylvan populations of T. dimidiata in the Yucatan state, Mexico, whereas in the Peten, Guatemala, it can reach up to 25% in sylvan populations. 4,17 In this work, we found natural infection of 38%; these data are similar to those results in the work by Ramirez-Sierra and others, 3 which reported 34% natural infection in a rural community in the Yucatan state, Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In the Yucatan Peninsula of Mexico, cryptic species were found; specimens from Yucatan should be considered as separate species rather than T. dimidiata. 2 Several studies have shown that the vector population in the domestic and peridomestic cycles in the Yucatan Peninsula comes from sylvan stocks and presents clear seasonality [3][4][5][6][7] . In this cycle of transmission, several reservoirs are involved: infected Didelphys virginiana and Peromyscus leucopus have been found in the sylvan cycle, and in the peridomestic and domestic cycles, Canis familiaris, Rattus rattus, Mus musculus, and humans have been found at different rates.…”
Section: Introductionmentioning
confidence: 99%
“…Vector control interventions, including conventional indoor residual insecticide spraying, peridomicile management, and the installation of insect screens and insecticide-impregnated curtains, were then applied to subsets of houses, and triatomine abundance in the houses was monitored for up to two consecutive infestation seasons. First, because of each house's location in the village, and particularly each house's distance from the surrounding forest/bushes, is a key factor for house infestation by non-domiciliated triatomines, 31 we ensured that houses receiving control interventions were located at a comparable distance from the periphery as houses without vector control interventions (permutation test P = 0.13, P = 0.39, and P = 0.10 in the villages of Sudzal, Teya, and Bokoba, respectively) and thus were exposed to a comparable risk for infestation.…”
Section: Housing Characteristicsmentioning
confidence: 99%
“…Where insects are transiently present and/or in very low density in the domestic habitat, community participation has been found highly reliable for entomologic surveys and also shown to be more sensitive than manual collection (Barbu et al, 2010;Ramirez-Sierra et al, 2010). Although we initially chose manual collection, it was performed by the same person to avoid operator bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies that explicitly take into account the spatial dimension remain rare. For example, Ramirez-Sierra et al (2010) studied domiciliary infestation of four villages on the Yucatan peninsula, Mexico with regard to insect sex, infection status and distance between houses and the village boundary, the latter variable being suggested by observations and the outcome of a model proposed by Slimi et al (2009). In a comparable way, Roux et al (2009) used several attributes to explicitly characterise the spatial structure of a Brazilian village in the semi-arid region of Bahia: (i) distance to the village centre; (ii) distance to the specific house where the majority of the insects was found; and (iii) relative situations of the domiciliary unit (central or peripheral and connected or isolated).…”
mentioning
confidence: 99%